2013
DOI: 10.1093/bioinformatics/btt107
|View full text |Cite
|
Sign up to set email alerts
|

PLncDB: plant long non-coding RNA database

Abstract: PLncDB is freely accessible at http://chualab.rockefeller.edu/gbrowse2/homepage.html and all results can be downloaded for free at the website.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 39 publications
1
117
0
Order By: Relevance
“…Moreover, an updated version of the Noncode database is now available as Noncode v4.0 (Xie et al 2014). Also we note that, apart from the resources reviewed here, other specific tools and databases exist, such as PLncDB (plant related lncRNAs) (Jin et al 2013), NRED (noncoding expression database) (Dinger et al 2009), and Linc2go ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an updated version of the Noncode database is now available as Noncode v4.0 (Xie et al 2014). Also we note that, apart from the resources reviewed here, other specific tools and databases exist, such as PLncDB (plant related lncRNAs) (Jin et al 2013), NRED (noncoding expression database) (Dinger et al 2009), and Linc2go ).…”
Section: Discussionmentioning
confidence: 99%
“…We used plant long noncoding RNA database (PLncDB) to browse the high through-put datasets (Jin et al, 2013). RNA-seq or ChIP-seq sequences were aligned to the TAIR10 genome using TopHat, SAMtools, BEDTools, and a custom PERL script (Li et al, 2009;Quinlan and Hall, 2010).…”
Section: Analysis Of Rna-seq Datasetsmentioning
confidence: 99%
“…BigWig-formatted files were integrated into PLncDB. Construction methods of PLncDB were described in our previous study (Jin et al, 2013).…”
Section: Analysis Of Rna-seq Datasetsmentioning
confidence: 99%
“…[8][9][10] A recent study reported 6,480 long intergenic non-coding RNAs (lincRNAs) in Arabidopsis, 11 which have been made available in PLncDB (the plant long non-coding RNA database). 12 On the other hand, the functional significance of the RNA molecules has been suggested to be embedded in the well-organized structures. 13 Thus, one question was raised whether these lncRNAs could form internal structures for certain biological outputs, such as sRNA production just like pri-miRNAs.…”
Section: Introductionmentioning
confidence: 99%